Accountability in The Maqashid Sharia Perspective - Satria Darma; Sunardi Sunardi; Alimuddin HM Alimuddin HM (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2022)
This study aims to analyze accountability in the perspective of maqashid sharia. In this study using exploratory study method, namely descriptive analysis in analyzing secondary data related to these problems, by determining the theory of Islamic companies, agency theory and information asymmetry, and the philosophy of justice in Islamic law. The results of the research show that accountability is carried out by the company as a form of accountability for the trust given. The goal is to create justice and prosperity for all parties.